PERAN PROFESI AKUNTAN DALAM MENGHADAPI ERA SOCIETY 5.0 - Hana Hayati; Gunawan Aji (Kampus Akademik Publiser, 2024)
The world is currently entering the era of society 5.0, which is characterized by the ease with which humans can access things through technology, systems and robots. In this era, the existence of accountants is predicted to decline due to competition with artificial sophistication. This research aims to understand the description of the accounting profession in the era of society 5.0, the technology used and the efforts that must be prepared. The research method used is data collection originating from a literature review with a qualitative approach. The research results show that accountants approaching 5.0 have broader duties than previous accountants. Accountants in this era must be able to adapt to existing technology and have the obligation to upgrade their skills and take advantage of existing opportunities. Therefore, an accountant must have skills in the field of information technology in order to be able to maintain its existence.